2007
DOI: 10.1111/j.1749-7345.2006.00074.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Daily Feeding Ratio on Growth and Body Composition of Subadult Olive Flounder, Paralichthys olivaceus, Fed an Extruded Diet during the Summer Season

Abstract: A 10‐wk feeding trial to determine the effect of daily feeding ratio on growth and body composition of subadult olive flounder fed the extruded pellet (EP) was performed during the summer season. Thirteen flounder (an initial body weight of 319 g) per tank were distributed into fifteen 500‐L flow‐through tanks. Five treatments of feeding ratio in 5% decrement were prepared in triplicate: 100 (satiation), 95, 90, 85, and 80% of satiation. Fish in the control group (100% of satiation) were hand‐fed to apparent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
2
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 27 publications
6
37
2
6
Order By: Relevance
“…Fish appear to continuously increase in weight commensurate with feeding rate up to the level of satiation, although this increase may not correspond with incremental feed consumption. Continuous weight gain in response to increased feeding rate has been reported in blackspot seabream (Pagellus bogaraveo; Ozorio et al, 2009); olive flounder (P. olivaceus; Cho et al, 2007); white sturgeon (Acipenser transmontanus; Deng et al, 2003); and gilthead sea bream (Spurus aurata; Mihelakakis et al, 2002), among other species. However, the improvement in growth performance of fish fed at a rate below satiation varied according to fish size.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Fish appear to continuously increase in weight commensurate with feeding rate up to the level of satiation, although this increase may not correspond with incremental feed consumption. Continuous weight gain in response to increased feeding rate has been reported in blackspot seabream (Pagellus bogaraveo; Ozorio et al, 2009); olive flounder (P. olivaceus; Cho et al, 2007); white sturgeon (Acipenser transmontanus; Deng et al, 2003); and gilthead sea bream (Spurus aurata; Mihelakakis et al, 2002), among other species. However, the improvement in growth performance of fish fed at a rate below satiation varied according to fish size.…”
Section: Discussionmentioning
confidence: 92%
“…Diet costs can represent between 30% and 70% of the total operating cost of an aquaculture enterprise: the proportion increases commensurate with the intensity of the operation (Webster et al, 2001). Feed intake is perhaps the principal factor affecting the growth rate of fish (Li et al, 2004); several studies have demonstrated that growth correlates to food intake (Mihelakakis et al, 2002;Cho et al, 2007;Kim et al, 2007;Ozorio et al, 2009). Ensuring an adequate supply of nutritionally balanced feed is critical for optimum growth, survival, disease immunity, dress-out yield, and the organoleptic properties of the flesh.…”
Section: Introductionmentioning
confidence: 99%
“…A taxa alimentar não influenciou a sobrevivência dos peixes que foi de 100% em todos os tratamentos, resultado semelhantes ao encontrados por Cho et al (2007), que não observaram mortalidade quando trabalharam com Paralichthys olivaceus.…”
Section: Resultsunclassified
“…Os robalos alimentados com a menor taxa de alimentação apresentaram menor crescimento, o que também ja foi observado em outras espécies, como o robalo europeu Dicentrarchus labrax (EROLDOGAN et al, 2004) e a perca, Perca fluviatilis, (FIOGBÉ; KESTMONT, 2003), sugerindo que a taxa alimentar de 1% não consegue oferecer nutrientes suficientes para suprir a demanda energética de manutenção basal do peixe, juntamente com a utilização destes nutrientes para um crescimento satisfatório.…”
Section: Resultsunclassified
“…Kim and Lee 2004), (Kim et al 2002a;Cho 2005;Cho et al 2006b), (Cho et al 2006a(Cho et al , 2007aKim et al 2009), (Kikuchi et al 1994(Kikuchi et al , 1997Kikuchi 1999aKikuchi , 1999bKim et al 2011) . Lee et al 1998;Kim et al 2000), (Scutellaria baicalensis)…”
mentioning
confidence: 99%